Side hustles in the COVID-19 era. A preliminary investigation in UK and Thailand on informal and part-time work during a period of employment turmoil - Azavedo, Mark (Technium Social Sciences Journal, 2022)
The study’s aim was to consider the motivations of workers who work part-time, work the gig economy, work informally and may have entrepreneurial aims in UK and Thailand. The notion of a side hustle to the main work, included where that main work was seen as, for instance, being a parent or other carer. Main work was not classified by level of earnings but by participant perception. In some cases there was no main job just “side” work, often whatever participants could get during the COVID era. Discussion with participants proceeded online and face to face in person. Some participants also completed a questionnaire, so producing a clear objectification for a core of participants, descriptive statistics. Otherwise the study was firmly qualitative in approach. The core descriptive statistical approach was very focused in an extensive Likert scale on motivations. Participants considered money the main motivation, whichever country and whatever the demographic of the participant. Sociability was generally seen as the lowest motivator, fifth of five potential motivators offered in the Likert Scale. Wider discussion with the core participants and others covered partly the same ground as the Likert, but participants introduced other themes for consideration, to include women’s empowerment and parenting.